How to Make Higher Education Institutions Innovative: An Application of Market Orientation Practices. Issue 3 (27th May 2019) - Vaikunthavasan, Sathana; Jebarajakirthy, Charles; Shankar, Amit
ABSTRACT: In the present era, higher education is considered a booming and significantly contributing sector to the economy of many countries. Due to the intense competition prevailing in the higher education sector, higher education institutions need to become market oriented and innovate in courses, delivery methods and student support services. Consequently, they could meet increasing expectations placed on them for quality of education and support services. The main aim of this study is to investigate the influence of both market orientation and its dimensions, on innovation in higher education institutions. This study also considered the age of the faculty a moderator to these influences. The sample comprised 270 managers and course cordinators attached to faculties, schools or units in Sri Lankan higher education institutions. The surveys were administered for data collection. The study has several contributions to the literature- all the three dimensions of market orientation, significantly and positively influenced innovation in higher education institutions. The age of the faculty significantly moderated the influence of both market orientation and its dimensions (Intelligence Generation and Responsiveness), on innovation. This study also expand the focus of theory of six sigma by applying it from market orientation and customer orientation perspectives. Finally, this study has modified items measuring several constructs to suit the higher education context which can be used by future researchers. From the findings, several practical implications are given to officials in higher education institutions for innovating in courses, delivery methods and support services. The article concludes with many useful directions for future researchers.